Інформаційні технології моделювання напівпровідникових структур - Лашко, Е. І.; Стрілкова, Т. О. (My University, 2025)
The work is dedicated to the study of the application of information technologies for modeling donor-acceptor semiconductor structures for the development of materials for photodetectors, lasers, and high-speed electronics. It presents the capabilities of Mathcad and GaussView 6 for analyzing the spatial structure of semiconductors, electronic levels, and energy characteristics. The study also explores spatial and energy structures of semiconductors used in optoelectronics, providing valuable insights for the design and improvement of optoelectronic devices.
Keywords: моделювання напівпровідникових структур; donor-acceptor semiconductor